An Economic Value of Waste for Informal Garbage Collectors and Community’s Perception Regarding Environmental Sustainability; A Case Study of Faisalabad-Pakistan - Muhammad Ashfaq, Muhammad Hassan Mahboob, Sahar (International Journal of Economic and Environment Geology, 2019)
This study analyzed economic value of solid waste for informal garbage collectors. It also evaluates community’s perception for better environment. Although waste management and environmental sustainability is a worldwide problem, but Faisalabad’s residents also face problems regarding solid waste, environment, clean water and clean air. The main objectives of this paper, which has been explored; to study the socio-economic characteristics of the respondents, to evaluates the resident’s perception regarding better environment and also estimate the income level of garbage collectors and significant determinants of income which they generate through waste collection. Data were collected from 125 households and 125 informal garbage collectors from different parts of (7 districts) Faisalabad in the month of January and February 2019 through well-developed questionnaire. The results of the socio-economic characteristics of the respondents were drawn through SPSS and adult males, females having low level of education were in the majority in waste collectors. Five categories (Waste collectors, (W. Cs), call on scavengers (CSs), transfer point pickers (TPPs), Street pickers (SPs) and dumpsite pickers (DPs) were studied. They were generating reasonable income; most of them were generating income above 20,000 rupees per month by working on average 7 to 8 hours per day. The garbage was being collected from streets, households, institutions, factories, hospitals and markets through different instruments and sold to middle man or factories. Garbage collectors face many social problems like sexual harassment for female garbage collectors and chances of occurrence of diseases during their work much likely to happen. Informal garbage collectors were uneducated as compared to residents who give their perception regarding environment. Majority of the residents blamed themselves for poor management of solid waste which leads to low level of environmental sustainability. Lack of awareness of the residents was the critical factor for better environment. In the second part; Ordinary least square (OLS) method was used to check the impact of different factors affecting their income level. Working hours has significant impact on income level except others (gender, age and equipment of collection). The policy makers should increase the awareness among masses regarding the improvement of environment by better management. There should also be awareness program for garbage collectors regarding health hazards by involving NGOs and others volunteers